PERBANDINGAN PENYELESAIAN SENGKETA BISNIS DALAM MASYARAKAT EKONOMI ASEAN (MEA) MELALUI ARBITRASE DI INDONESIA (BANI) DAN SINGAPURA (SIAC) - NIM. A1011171210, AGUS FIRMANSYAH (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT The use of arbitration as an alternative mode of dispute resolution is increasingly being used in Indonesia and internationally. Regarding the procedures for implementing arbitration awards in Indonesia, they are differentiated based on the type of award, namely national arbitration awards or international arbitration awards as regulated in Article 1 number (9) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The current problem is that business people, both domestic and international, in resolving business disputes they prefer dispute resolution through arbitration institutions, especially SIAC compared to arbitration institutions such as BANI. The title of this research is Comparison of Business Dispute Resolution in the ASEAN Economic Community (AEC) Through Arbitration in Indonesia (BANI) and Singapore (SIAC). The type of research used is a Normative research method using literature study, namely by reading various literature related to the process. arbitration settlement in related countries, Problem formulation